UTILIZATION OF SONG LYRICS IN “TIKTOK” IN TEACHING VOCABULARY FOR SENIOR HIGH SCHOOL STUDENTS - Diky Ari Pratama; Yunik Susanti; Suhartono (Media Inovasi Pendidikan dan Publikasi, 2024)
Mastering English vocabulary has its own challenges, especially in Indonesia where English is a foreign language. To help students master vocabulary, educators need to design interesting learning media. The researcher have used the